2014
DOI: 10.1371/journal.pone.0089303
|View full text |Cite
|
Sign up to set email alerts
|

Enamelin Is Critical for Ameloblast Integrity and Enamel Ultrastructure Formation

Abstract: Mutations in the human enamelin gene cause autosomal dominant hypoplastic amelogenesis imperfecta in which the affected enamel is thin or absent. Study of enamelin knockout NLS-lacZ knockin mice revealed that mineralization along the distal membrane of ameloblast is deficient, resulting in no true enamel formation. To determine the function of enamelin during enamel formation, we characterized the developing teeth of the Enam−/− mice, generated amelogenin-driven enamelin transgenic mouse models, and then intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 25 publications
(34 reference statements)
1
61
0
Order By: Relevance
“…The most outer enamel was less mineralized when compared with the control tooth, as outer enamel appeared darker in RA-treated animals. Enamel rods of RA-supplemented animals were less densely packed, and as a consequence, areas normally filled with interprismatic enamel seemed empty and showed holes-like pattern (Figure 2H), similar to Enam haploinsufficent mice (Hu et al, 2014). …”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The most outer enamel was less mineralized when compared with the control tooth, as outer enamel appeared darker in RA-treated animals. Enamel rods of RA-supplemented animals were less densely packed, and as a consequence, areas normally filled with interprismatic enamel seemed empty and showed holes-like pattern (Figure 2H), similar to Enam haploinsufficent mice (Hu et al, 2014). …”
Section: Resultssupporting
confidence: 52%
“…When RA treatments were performed from E12.5 to 16.5, they were found to produce a chalky lightening and length reduction of incisors, changes more pronounced in lower incisors (Figures 1B,F). The whiter color and less shiny surface may reflect reduced enamel thickness typical of mouse enamel hypoplasia models (Gibson et al, 2001; Masuya et al, 2005; Hu et al, 2014). Treatments performed at later stages (E13.5–16.5: Figures 1C,G, or E14.5–17.5: Figures 1D,H) had less severe effects on enamel, suggesting RA has early roles in the oral epithelium starting at the placode stage of tooth initiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al [2014] suggested that the enamelin protein is essential for the formation of crystals with prism structures and obtaining optimal thickness of the enamel. Defects in the ENAM gene during evolution are associated with defective enamel formation [Meredith et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Porcine DGP possesses one glycosylated asparagine and 4 phosphorylated serine residues [23]. DPP specifically binds to collagen fibrils [3335] and can act as a mineralization promoter or inhibitor at low and high concentrations, respectively [36].…”
Section: Introductionmentioning
confidence: 99%